Studi Ttranslokasi Asimilat pada Padi: Pendekatan Untuk Meningkatkan Produktivitas di Lingkungan Optimal - Restu Mumpuni (Fakultas Pertanian Universitas Almuslim Bireuen Aceh, 2025)
The rice productivity can be increased by improving the efficiency of absorbing translocation in plants. In rice, assimilates are translocated from the leaves to the plant's stem, roots, and panicles. Effective coordination among plant components is necessary for this process to guarantee that assimilation is distributed efficiently by plant growth and development requirements. This mini-review aims to provide additional information regarding the behavior and process of assimilate translocation in rice under optimum circumstances, which may be utilized as a guide in increasing rice productivity. Sink strength, spikelet partitioning in panicles, blooming duration, and the presence of certain genes in rice cultivars are some factors that influence the translocation of assimilate in rice plants. The features of rice varieties, the availability of nitrogen, and the soil's fertility can all be considered when optimizing the relationship between source and sink to maximize production and resource utilization in rice cultivation. In assimilate translocation, nutrients can be managed by applying nutrients at the right time, strengthening sources and sinks, and enhancing non-structural carbohydrates. Increased plant population, application of organic fertilizer, use of intermittent irrigation patterns, and application of nitrogen fertilizer are among the cultivation techniques that can enhance source and sink interactions in rice.